A deep black breath - Goh, Ernest Chang Zheng (2018)
A Deep Black Breath began with a photographic investigation into the state of my mind. Through a process not unlike meditation, the camera was used as a tool to capture images that on hindsight revealed my preoccupation with death. The images were captured during periods where the situation presented visual metaphors or evocations of feeling that communicated my obsession with death. A Deep Black Breath begins from that realisation, addressing the fear that haunted me when recalling a near drowning experience. The video installation hopes to confront, not with an answer, but with the perennial question, what is the nature of death and how do we live knowing that we are going to die?